Optimising building envelope and insulation materials for energy efficiency and life-cycle cost in Cypriot residences - Mohamadi, Yashar; Celik, Tahir; Celik, Tolga (Taylor & Francis Ltd, 2024)
Residential buildings consume approximately 36% of total electricity consumption in Cyprus and this is expected to continue increasing in the coming years. This study explores the potential for energy savings in residential buildings in Cyprus through optimising building envelopes and insulation materials. Using building information modelling and energy modelling software, the study analyses 120 combinations of building envelopes and eight insulation materials, identifying an optimal combination of wall, roof, and flooring materials that could result in 32% energy load reductions and 27% lower life-cycle costs compared to the median scenario. High-density rock wool insulation on roofs and double-glazed windows were also found to offer both monetary and energy performance benefits. A sensitivity analysis revealed that the current high energy prices could provide greater economic incentives to adopt these optimisation strategies. Optimising building materials in Cyprus could play a critical role in climate strategy while also offering significant economic benefits.
Keywords: Energy efficiency; cypriot residences; building information modelling; building envelope materials; insulation materials; thermal comfort